Draft report on the consultants' review of the structure and functioning of the Caribbean Community Secretariat (CCS GeorgetownGY, 2002)
Reviews the consultants' report titled Review of the Structure and Functioning of the Caribbean Community Secretariat.
Keywords: CARICOM